Regulation of Acetate Metabolism in a Strain of Acinetobacter sp. Growing on Ethanol - Pirog, Tatiana; Kuzminska, Yu. (My University, 2003)
Ethanol metabolism in Acinetobacter sp. is shown to be limited by the rate of acetate assimilation,a reaction catalyzed by acetyl-CoA synthetase (EC 6.2.1.1). Effects of ions (sodium, potassium, and magnesium), by-products of ethanol and acetaldehyde oxidation (NADH and NADPH), and pantothenic acid on this enzyme are studied (sodium, NADH, and NADPH inhibit acetyl-CoA synthetase; pantothenic acid, potassium, and magnesium act as enzyme activators). Conditions of culturing were developed under which ethanol, acetaldehyde, and acetate in Acinetobacter cells were oxidized at the same rates, producing a threefold increase in the activity of acetyl-CoA synthetase in the cell-free extract. The results of studies of acetyl-CoA synthetase regulation in a mutant strain of Acinetobacter sp., which is incapable of forming exopolysaccharides, provide a basis for refining the technology of ethapolan production involving the use of C2 substrates.
Keywords: ethanol; етанол; ацетат; acetate; етаполан; екзополісахарид; кафедра біотехнології і мікробіології